Antisynthetase syndrome with rare EJ‐1 antibodies with antiphospholipid syndrome. Issue 7 (13th June 2022) - Chhor, Louis; Tu, Steven; Fogarty, Paul; Fong, Christopher
Abstract: We describe the first case of antisynthetase syndrome (ASS) with antibodies to anti‐glycyl tRNA synthetase (EJ‐1) with antiphospholipid syndrome (APLS). A 66‐year‐old man presented with progressive dyspnoea, fever, dry cough and proximal muscle weakness over several months on a background of cryptogenic organizing pneumonia. Examination revealed bibasal fine chest crackles, proximal muscle weakness of the upper and lower limbs, digital skin thickening and facial telangiectasias. Creatine kinase was elevated and autoimmune screening was positive for anti‐EJ‐1, anti‐beta‐2‐glycoprotein, anti‐Ro and anti‐La antibodies. Computed tomography of the chest revealed a usual interstitial pneumonia pattern and a ventilation–perfusion scan demonstrated scintigraphic evidence of bilateral pulmonary emboli. A diagnosis of ASS and APLS was made. Immunosuppressive therapy including pulsed methylprednisolone, rituximab and mycophenolate was commenced with improvement in symptoms. This case highlights the importance of evaluation for ASS in idiopathic interstitial pneumonia, and APLS in ASS patients. Abstract : To our knowledge, we describe the first case of antisynthetase syndrome with antibodies to anti‐glycyl tRNA synthetase (EJ‐1) with antiphospholipid syndrome.